Translation and validation of the Moral Sensitivity Questionnaire in the Greek language - Panayiotou, Andrie; Papamichael, Maria; Elia, Stavria-Artemis; Karanikola, Maria (My University, 2020)
Moral sensitivity is the ability to recognize ethical challenges and dilemmas when raised, both in everyday and professional life. Within the healthcare setting, moral sensitivity is a core value and a necessary skill in order to both identify “vulnerable” patients and /or family members, and to reflect on professional actions. However, data on moral sensitivity in health professionals are scarce. To be able to quantify moral sensitivity, an appropriate tool was searched for and the “Moral Sensitivity Questionnaire” (MSQ) developed by Lutzen et al. was identified. The MSQ-revised version was used; a short self-administered questionnaire of 9 items covering the three main components of moral sensitivity: sense of moral burden (4 items), moral strength (3 items) and moral responsibility (2 items). The ratings of the items (6 point Likert-scale) are added, with a higher score indicating higher ethical sensitivity. The MSQ was not available in Greek, so following permission; it was translated and validated for use in Greek according to standard protocols. First it was independently translated by two researchers, a common translation agreed and that version was back-translated to English by a third researcher and compared to the original. Finally, it was validated by test-retest in 10 students one week apart.
Keywords: Bioethics; Moral sensitivity